Analisis Pemilihan Supplier Chemical Boilout Menggunakan Metode AHP (Analytical Hierarchy Process) Di Seksi Paper Machine#6. - Satriardi; Martinus S (Fakultas Teknik UMRI, 2021)
This study aims to determine the best criteria on which to base the selection of alternative Chemical Boilout suppliers for Paper Machine # 6 dissection and to determine the best supplier to be selected for the Chemical Boilout supplier. The benefit of this research is to improve the consistency of run-ability by reducing the lost time sheet break and paper rejects. The method used is data processing using AHP (Analytical Hierarchy Process) and data collection by means of observation, interviews and questionnaires. The results of this study indicate the criteria for supplier selection, namely quality, price, supplier performance and guarantee of product claims. Then produce a weight for each alternative supplier, in order, namely kemira supplier with a weight of 30.627%, buckman with a weight of 29.973%, solenis with a weight of 21.608% and amazone with a weight of 17.792%. therefore for the best supplier and will be recommended to be selected in the upcoming tender process is the supplier Kemira.